Constitutional Law around the globe: judicial review in the United States and the “writ of certiorari” - Diniz Araújo, Luiz Henrique (Revista de Investigações Constitucionais, 2020)
This paper exploring the writ of certiorari in the United States Constitutional Law is the second of the series “Constitutional Law Around the Globe”. This section of the series focuses on “Judicial Review and the Filters to Access Supreme and Constitutional Courts”. The first paper in the row, published in the year 2019, analyzed the Constitutionality Priority Question (Question Prioritaire de Constitutionnalité – QPC) in France. In this second paper, we analyze how the U.S. Supreme Court picks cases from thousands that reach it every year and the strategies that the Court adopts to filter these cases. The paper focuses specifically on Rule 10, the “writ of certiorari” and their operation in practice.